2017
DOI: 10.2147/copd.s150243
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation affects the natural history of COPD

Abstract: BackgroundCigarette smoking is the most commonly encountered and readily identifiable risk factor for COPD. However, it is not clear which quantitative factors related to smoking influence the prognosis of COPD patients.MethodsA total of 204 patients with a long-term history of smoking were enrolled into this study and followed up for 5 years. Patients were divided into “death” or “survival” groups based on follow-up results and “quitting-smoking” or “continuing-smoking” groups based on whether they gave up sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 26 publications
2
37
0
2
Order By: Relevance
“…The results from our current model were interesting and present a hypothetical view of how the next 10 years would unfold for the patient, for whom we had only one year of observation. Despite the short follow-up period, our results are consistent with documented literature on how smoking affects the natural progression of COPD (Bai et al 2017) and serve as a validation to the model. The implication from these results for Bulgaria would lead us to believe that a national smoking cessation programme should be implemented, as well as encouraging patients to seek professional help at earlier stages, since Gold A patients have the best disease control of non-smokers and tend to live longer.…”
Section: Discussionsupporting
confidence: 88%
“…The results from our current model were interesting and present a hypothetical view of how the next 10 years would unfold for the patient, for whom we had only one year of observation. Despite the short follow-up period, our results are consistent with documented literature on how smoking affects the natural progression of COPD (Bai et al 2017) and serve as a validation to the model. The implication from these results for Bulgaria would lead us to believe that a national smoking cessation programme should be implemented, as well as encouraging patients to seek professional help at earlier stages, since Gold A patients have the best disease control of non-smokers and tend to live longer.…”
Section: Discussionsupporting
confidence: 88%
“…13 Among different factors, duration of smoking seems to be an important one. 14 Quitting smoking helps in prolonging survival, as evident from previous researches, probably by relieving emphysema. 14,15 As India documented a reduction in smoking prevalence from 34.6% to 28.6% among citizen aged 15 years and older, it is expected to reduce the burden of COPD in future.…”
Section: Discussionmentioning
confidence: 82%
“…14 Quitting smoking helps in prolonging survival, as evident from previous researches, probably by relieving emphysema. 14,15 As India documented a reduction in smoking prevalence from 34.6% to 28.6% among citizen aged 15 years and older, it is expected to reduce the burden of COPD in future. 6 Since SHS increased the risk of COPD mortality, the benefit of smoking reduction could be multifold.…”
Section: Discussionmentioning
confidence: 82%
“…There is a consensus in literature about the great importance of early COPD diagnosis, enabling the establishment of measures that may alter the course of the disease, including pharmacological and non-pharmacological interventions and smoking cessation. 7 11 Assessment of respiratory obstruction in the early stages is critically dependent on the sensitivity of pulmonary function tests. 12 It has previously been observed that spirometric indices are not sensitive to small changes due to smoking.…”
Section: Introductionmentioning
confidence: 99%